2009
DOI: 10.1111/j.1468-3148.2008.00467.x
|View full text |Cite
|
Sign up to set email alerts
|

The Reliability, Validity and Practical Utility of Measuring Supports using the I‐CAN Instrument: Part II

Abstract: Background There is an urgent need for developing reliable, valid and practical instruments that assess and classify the support needed by persons with disability to function in their chosen living, working and social environments. I-CAN is an instrument that addresses the frequency and level of support needed (not individual skills or deficits) for each individual with a disability. Method Studies were conducted to assess the test-retest reliability and inter-rater reliability. Concurrent validity was investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 15 publications
0
13
0
1
Order By: Relevance
“…Wehmeyer et al (2012) found that their participants with physical disabilities scored higher in 'Home Living', 'Community Living' and 'Health and Safety'. Riches et al (2009) used the I-CAN, another measure of support needs, and found that three of the domains with the greatest support needs were 'Self-Care and Domestic Life', 'Community' and 'Social and Civic Life'.…”
Section: Discussionmentioning
confidence: 99%
“…Wehmeyer et al (2012) found that their participants with physical disabilities scored higher in 'Home Living', 'Community Living' and 'Health and Safety'. Riches et al (2009) used the I-CAN, another measure of support needs, and found that three of the domains with the greatest support needs were 'Self-Care and Domestic Life', 'Community' and 'Social and Civic Life'.…”
Section: Discussionmentioning
confidence: 99%
“…Instead, suggestion is made that medical and behavioural support needs should be considered separately in resource allocation applications. A concurrent validity study using earlier versions of the I-CAN (Riches et al 2009b) compared to the ICAP found high correlation between these two assessments, except in the I-CAN Physical Health and Mental & Emotional Health domains. These two domains are likely to be key drivers of the level of support need and are also domains found to be more likely to fluctuate over time (Riches et al 2009b).…”
Section: Validation Of Support Needs Instrumentsmentioning
confidence: 99%
“…A concurrent validity study using earlier versions of the I-CAN (Riches et al 2009b) compared to the ICAP found high correlation between these two assessments, except in the I-CAN Physical Health and Mental & Emotional Health domains. These two domains are likely to be key drivers of the level of support need and are also domains found to be more likely to fluctuate over time (Riches et al 2009b). The ICAP does not include comparable domains in its calculation of a service level need score, which is based solely on the adaptive and maladaptive behaviour domains.…”
Section: Validation Of Support Needs Instrumentsmentioning
confidence: 99%
See 2 more Smart Citations